A Comparative Study between Flapped and Flapless Surgical Techniques in Dental Implant Stability According to Resonance Frequency Analysis - Hassan, Ali F; Abdul-Lateef, Thair (Journal of Baghdad College of Dentistry, 2016)
Background: Recent implant surgical approach aims to cause less trauma, invasiveness and pain as much as possible and to reduce patient and surgeon discomfort, time of surgery and time needed for functional implant loading. Flapless surgical techniques considered recently as one of the most popular techniques that may achieve these aims especially enhancing osseointegration and subsequently implant stability within less time than the traditional flapped surgical technique. So this study aimed to make a comparison between flapped and flapless surgical techniques in resulted implant stability according to resonance frequency analysis RFA and in duration of surgical operation. Materials and methods: A total of 26 patients with 41 implants (one implant in the study group failed so it was excluded from the statistical analysis) were randomized into two groups: control group which involved 20 implants inserted by conventional flapped surgical approach and study group which involved 20 implants inserted by flapless surgical approach. Estimation of alveolar bone was done for study group by bone (ridge) mapping procedure. Duration of surgical operation for each implant, Implant stability was measured at three time intervals (at surgery, two months and three months after surgery). Results: After three months interval of surgery the mean implant stability of the study (flapless) group achieved significant higher implant stability than control (flapped) group (P< 0.05) and the difference in measured implant stability was (5.05) implant stability quotient(ISQ). The time of surgical operation for implants in the study group significantly was less than that of control group (P< 0.01). Conclusions:implants placed with flapless surgical technique can produce high implant stability in shorter time and consume prominently shorter time for surgical operation compared to those placed with conventional flapped technique.